1998
DOI: 10.1111/j.1749-6632.1998.tb09686.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antiglycolipid Antibodies in Neurological Disordersa

Abstract: Glycolipids have been shown to be antigens for circulating antibodies in autoimmune processes affecting the nervous system like neuropathy associated with IgM paraproteinemia, Guillain Barré syndrome (GBS), multifocal neuropathy, and variants thereof. The antibody titers, the Ig-classes, and the antibody specificity vary between studies and disease groups. The immunogens are in general unknown. However, GBS is often associated with an infection with Campylobacter jejuni, which expresses a lipopolysaccharide st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Studies describing the cellular and subcellular distribution of sulfatide are of importance in elucidating its general functions as well as its relation to autoimmune pathology. High serum titers of sulfatide antibodies have, for example, been found to be associated with diabetes type 1 (Buschard et al, 1993a), HIV (Gisslen et al, 1999), and peripheral neuropathies, only some of which have prominent demyelination (Willison, 1994; Fredman, 1998). A prerequisite for a pathological role of sulfatide autoantibodies is that the antigen is accessible to the circulating antibodies, which can be investigated by immunohistochemical analyses of peripheral nerves.…”
mentioning
confidence: 99%
“…Studies describing the cellular and subcellular distribution of sulfatide are of importance in elucidating its general functions as well as its relation to autoimmune pathology. High serum titers of sulfatide antibodies have, for example, been found to be associated with diabetes type 1 (Buschard et al, 1993a), HIV (Gisslen et al, 1999), and peripheral neuropathies, only some of which have prominent demyelination (Willison, 1994; Fredman, 1998). A prerequisite for a pathological role of sulfatide autoantibodies is that the antigen is accessible to the circulating antibodies, which can be investigated by immunohistochemical analyses of peripheral nerves.…”
mentioning
confidence: 99%
“…Mounting evidence of high levels of anti‐GSL antibodies in the sera of patients with Guillain‐Barré syndrome (GBS), multifocal motor neuropathy (MMN), motoneuron diseases, chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), and a number of related neurological disorders has suggested that GSLs may play a role in the pathogenesis of these peripheral neuropathies (for reviews see Yuki, 1997; Fredman and Lekman, 1997; Willison et al, 1997; Vriesendorp, 1997; Yu and Ariga, 1998; Arasaki et al, 1998; Fredman, 1998; Baumann et al, 1998; Quarles and Weiss, 1999; Asbury, 2000; Hughes et al, 2000). Because antiganglioside antibodies, such as anti‐GM1, have been described in the sera of GBS patients, estimation of anti‐GM1 and the respective complement‐activating capacity may be helpful in the diagnosis of this inflammatory neuropathy (Uetz‐von Allmen et al, 1998).…”
Section: Peripheral Neuropathiesmentioning
confidence: 99%
“…To date, the role of anti‐GSL antibodies in autoimmune neuropathies continues to undergo remarkable development and expansion (for reviews see Yuki,1997; Yu and Ariga,1998; Fredman,1998; Asbury,2000; Ariga et al,2001; Willison and Yuki,2002; Ang et al,2004; Kieseier et al,2004). However, there has not been a systematic review of the correlation between anti‐GSL antibodies, clinical manifestation, and potential mechanisms that underlie GBS and related disorders.…”
mentioning
confidence: 99%